Escaping from a combination of liquidity trap and credit crunch - Frank Heinemann (Center for Economic Studies and ifo Institute (CESifo), 2008)
This brief exposition suggests that the Federal Reserve System temporarily guarantee a lower bound on stock prices in order to escape the current combination of liquidity trap and credit crunch. It shortly discusses reasons for this measure, consequences, and some alternatives. It is meant as a policy suggestion in case the recapitalization of banks, agreed upon in mid-October 2008, turns out to be insufficient for stabilizing financial markets and the downward spiral in asset prices resumes.
Keywords: E52; E58; E31; E44; G21; 330; Financial crisis; monetary policy; liquidity trap; credit crunch; asset markets; Liquiditätspräferenz; Kredit; Finanzmarktkrise; Geldpolitik; Börsenkurs; Börsenkrise; USA